Femtosecond-written long-period gratings in fluoride fibers - Heck, Maximilian; Nolte, Stefan; Tuennermann, Andreas; Vallee, Real; Bernier, Martin (Optics Letters, 2018)
Long-period gratings induced in fluoride glass fibers using femtosecond laser pulses at 800 nm are, to the best of our knowledge, demonstrated for the first time. By means of tightly confined ultrashort laser pulses, smooth periodic lines of refractive index changes are induced along the fiber core. Taking advantage of heat accumulation effects in the focal volume, attenuation peaks down to −24 dB, with sharp and predictable spectral resonances, were obtained. Thermal annealing of the grating up to 250°C yielded a significant reduction of the induced refractive index change. The gratings could find applications in various integrated mid-infrared optical devices, such as optical notch filters in fiber amplifiers.
CRIS-Team Scopus Importer:2023-04-20